Frailty and Fracture, Disability, and Falls: A Multiple Country Study From the Global Longitudinal Study of Osteoporosis in Women. Issue 3 (25th January 2013) - Tom, Sarah E.; Adachi, Jonathan D.; Anderson, Frederick A.; Boonen, Steven; Chapurlat, Roland D.; Compston, Juliet E.; Cooper, Cyrus; Gehlbach, Stephen H.; Greenspan, Susan L.; Hooven, Frederick H.; Nieves, Jeri W.; Pfeilschifter, Johannes; et al.
<x xml:space="preserve">Abstract</x> Objectives To test whether women aged 55 and older with increasing evidence of a frailty phenotype would have greater risk of fractures, disability, and recurrent falls than women who were not frail, across geographic areas (Australia, Europe, and North America) and age groups. Design Multinational, longitudinal, observational cohort study. Setting Global Longitudinal Study of Osteoporosis in Women (GLOW). Participants Women (N = 48, 636) aged 55 and older enrolled at sites in Australia, Europe, and North America. Measurements Components of frailty (slowness and weakness, poor endurance and exhaustion, physical activity, and unintentional weight loss) at baseline and report of fracture, disability, and recurrent falls at 1 year of follow‐up were investigated. Women also reported health and demographic characteristics at baseline. Results Women younger than 75 from the United States were more likely to be prefrail and frail than those from Australia, Canada, and Europe. The distribution of frailty was similar according to region for women aged 75 and older. Odds ratios from multivariable models for frailty versus nonfrailty were 1.23 (95% confidence interval (CI) = 1.07–1.42) for fracture, 2.29 (95% CI = 2.09–2.51) for disability, and 1.68 (95% CI = 1.54–1.83) for recurrent falls. The associations for prefrailty versus nonfrailty were weaker but still indicated statistically significantly greater risk of each outcome. Overall, associations between frailty and each outcome were similar across age and geographic region. Conclusion Greater evidence of a frailty phenotype is associated with greater risk of fracture, disability, and falls in women aged 55 and older in 10 countries, with similar patterns across age and geographic region.